Clinical and Socio-Demographic Predictors of Psychosocial Distress in Women with Breast Cancer in Nairobi, Kenya - Muriithi, Wanjiru; Kaaria, Zipporah; Mapesa, Job (International Journal of Professional Practice, 2024)
Research shows that 25%–50% of breast cancer patients worldwide experience distress, with some African countries reporting 71% and Kenya 34-50% distress cases. This study investigated clinical and socio-demographic predictors of breast cancer patients’ psychosocial distress. Poor quality of life outcomes, reduced adherence to treatment, and inferior clinical and psychosocial functioning are all associated with psychosocial distress. This study adopted an exploratory, sequential cross-sectional design. The study targeted 763, 18–70-year-old female breast cancer patients. Breast cancer patients, nurses, lay navigator, and oncologists were enlisted through opportunity sampling technique for collection of both the qualitative and the quantitative data. Interviews, focus group discussions, and questionnaires were used to collect data. Using a total score of >11, with NCCN cut-off mark of >4 for clinically significant distress; and >7 for severe distress, psychosocial distress was screened using distress thermometer and problem checklist. Notably, income and stage of diagnosis emerged as significant predictors of psychosocial distress, clinical anxiety, and depression. Income predicted severe distress (OR = 5.5, p = 0.001), anxiety (OR = 2.8, p = 0.004), depression (OR = 4.7, p = 0.001), and early diagnosis had an inverse relationship with distress (OR = 0.3, p = 0.006) and depression (OR = 0.5, p = 0.049). Still, testimonials showed that young women had more emotional distress, while elderly women had more physiological distress. Marriage provided two insurance policies. The study emphasises understanding of emotional and psychological distress factors, identifying patients who need extra help, and using psychotherapy and social interventions to alleviate suffering, enhance resilience, and improve treatment outcomes